AKTIVITAS ANTIBAKTERI BEDAK YANG DIPERKAYA DENGAN KONSENTRASI EKSTRAK BUAH Rhizopora mucronata - Omnia Farahna Sungkar; Safira Khanza; Rizki Aji Pangestu (Program Studi Teknologi Pangan, 2018)
Abstract Rhizopora mucronata is one of the mangrove species spread over the coastal areas of Indonesia, growing in the heavy swampy swamps that are located in the coastal plates and the growth is heard by the tides of the sea. This type of mangrove population is concentrated in the areas of Papua, Kalimantan, Sulawesi, and Sumatra. Even the mangrove population in Indonesia is exposed to 75% and the entire mangrove population of Asia Tengggara, or about 27% of the total world mangrove population. Mangrove is utilized optimally in this fruit source of tannin, flavonoid, saponin, fenol and hidrokuinon. The bioactive component may be used as an antibacterial applied in powder products. The purpose of this study was to conduct phytochemical and antibacterial activity of secondary metabolite extract of Rhizophora mucronata ethanol extract and its application to powder obtained from Kaliprau Village, Ulujami, Pemalang Regency, Central Java. This research was conducted in several steps, namely the process of maceration, evaporation, phytochemical test and antibacterial activity. The results of phytochemical studies showed that the metabolite compounds contained in the ethanol extract of Rhizophora mucronata fruit contain 65.630 ppm flavonoids, 4333 ppm phenol, 9.41% saponin, 21.11% alkaloids and positive steroids. flavonoids and alkaloids. Tests of antibacterial activity using Staphylococcus aureus and Escherichia coli bacteria were performed on concentrations of concentration 10%, 20%, 40%, 60%. This research was conducted in Analytical Laboratory, Faculty of Fisheries and Marine Science, Diponegoro University. The results showed that DDH of Rhizophora mucronata ethanol extract was most effective against the growth of S. aureus and E. coli bacteria at 40% at 60% concentration because of having DDH>8mm.